Genome-wide analysis of differential transcriptional and epigenetic variability across human immune cell types. Issue 1 (December 2017) - Ecker, Simone; Chen, Lu; Pancaldi, Vera; Bagger, Frederik; Fernández, José; Carrillo de Santa Pau, Enrique; Juan, David; Mann, Alice; Watt, Stephen; Casale, Francesco; Sidiropoulos, Nikos; Rapin, Nicolas; et al.
Abstract Background A healthy immune system requires immune cells that adapt rapidly to environmental challenges. This phenotypic plasticity can be mediated by transcriptional and epigenetic variability. Results We apply a novel analytical approach to measure and compare transcriptional and epigenetic variability genome-wide across CD14+ CD16− monocytes, CD66b+ CD16+ neutrophils, and CD4+ CD45RA+ naïve T cells from the same 125 healthy individuals. We discover substantially increased variability in neutrophils compared to monocytes and T cells. In neutrophils, genes with hypervariable expression are found to be implicated in key immune pathways and are associated with cellular properties and environmental exposure. We also observe increased sex-specific gene expression differences in neutrophils. Neutrophil-specific DNA methylation hypervariable sites are enriched at dynamic chromatin regions and active enhancers. Conclusions Our data highlight the importance of transcriptional and epigenetic variability for the key role of neutrophils as the first responders to inflammatory stimuli. We provide a resource to enable further functional studies into the plasticity of immune cells, which can be accessed from:http://blueprint-dev.bioinfo.cnio.es/WP10/hypervariability .